Luxury Fashion Consumption of Chinese Overseas Students: Motivation for Purchase - tang, yuxin (2016)
This dissertation aimed to answer the main research question: What are the motivations for Chinese overseas students to purchase luxury fashion products? After reviewing the literature, the motivation of luxury consumption mainly include social-oriented motivation and personal-oriented motivation (Leibenstein, 1950, Vigneron and Johnson, 1999). Through the qualitative research method, data was collected by in-depth interview from 12 Chinese overseas students in UK. The main motivations identified by this research reflect and support the academic theories proposed by other literatures. Chinese overseas students are motivated by social-oriented motivation (bandwagon effect, prestige value, conspicuous consumption, gift giving) and personal-oriented motivation (hedonic value, quality, self-expression). In addition, some specific motivations due to they living abroad were found. For example, the price advantage, the authenticity of the goods and more channels to purchase in UK are other specific motivations that drive them to purchasing luxury products. Finally, practical and managerial implications are further discussed.